2012
DOI: 10.1364/oe.20.007388
|View full text |Cite
|
Sign up to set email alerts
|

Confocal surface plasmon microscopy with pupil function engineering

Abstract: Surface Plasmon microscopy can measure local changes of refractive index on the micron scale. Interferometric plasmon imaging delivers quantitative high spatial resolution sensitive to refractive index. In addition the so called V(z) method allows image contrast to be controlled by varying the sample defocus without substantially degrading spatial resolution. Here, we show how a confocal system provides a simpler and more stable alternative. This system, however, places greater demands on the dynamic range of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 9 publications
0
26
0
Order By: Relevance
“…The experimental system is similar to that used in [5], except that here a phase SLM (BNS 512*512 phase SLM) is used to replace the amplitude SLM; its function will be described at length in the paper. Figure 1(b) shows a simplified schematic of the optical system.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…The experimental system is similar to that used in [5], except that here a phase SLM (BNS 512*512 phase SLM) is used to replace the amplitude SLM; its function will be described at length in the paper. Figure 1(b) shows a simplified schematic of the optical system.…”
Section: Methodsmentioning
confidence: 99%
“…We have shown that the lateral resolution of SP microscopy is optimized with an interferometric arrangement and we have more recently demonstrated that similar performance can be achieved with a confocal microscope arrangement [5]. Figure 1(a) shows a conceptual diagram of SP imaging in a confocal system, as the sample is defocused there are two principal contributions to the signal arising from paths P1 and P2, which interfere with each other at the pinhole.…”
Section: Introductionmentioning
confidence: 90%
See 3 more Smart Citations